Understanding street protests: from a mathematical model to protest management. - Sergei Petrovskii; Maxim Shishlenin; Anton Glukhov (PLoS ONE)
Street protests have been a common feature of human society for many centuries. They often act as a driver of social changes but they may also disrupt everyday life and lead to considerable economic losses. Understanding of factors that may affect the duration of street protests and the number of participants is a problem of pivotal importance. Mathematical modelling is an efficient research approach to study this problem. Here we present a novel modelling framework that takes into account heterogeneity of protesters behaviour and the effect of policing. Using the 2018-2019 Yellow Vest Movement in France as a case study, we show that our model is in a very good agreement with data. We also show that a moderate increase in the efficiency of police actions on particular days may have a significant effect on protest's intensity and duration. Our findings open a possibility for a more efficient protests management.